Efektivitas Aplikasi SafeTeens terhadap Peningkatan Literasi Kesehatan Mental Remaja: Studi Kuasi-Eksperimen - Sari, Tesha Hestyana; Jumaini, Jumaini; Putri, Syeptri Agiani; Kusumarini, Novita (Jurnal Ners, 2026)
Mental health problems among adolescents continue to increase, coupled with low levels of mental health literacy, which can lead to delays in seeking professional help. Innovative technology-based efforts are needed to ensure wider access to mental health information and services. This study aims to develop and test the effectiveness of the SafeTeens app as an educational tool for improving adolescent mental health literacy. The study used a quasi-experimental design with an intervention and control group. A sample of 60 adolescents was selected based on inclusion criteria and divided proportionally into two groups. The research instrument was a mental health literacy questionnaire that had been tested for validity and reliability. Data were analyzed using the Chi-Square test to determine differences in mental health literacy levels before and after the intervention. The results showed that the intervention group experienced a significant increase in mental health literacy levels after using the SafeTeens app (χ² = 19.14; p = 0.00007), whereas the control group showed no significant change (χ² = 0.66; p = 0.719). The SafeTeens app has proven effective in improving adolescents' understanding of mental health issues, distinguishing myths from facts, and how to seek appropriate help. This study recommends further development of the SafeTeens app with gamification features and periodic reminders to increase user engagement, as well as long-term testing to assess the sustainability of improvements in mental health literacy. Furthermore, cultural and local language adaptations need to be continuously refined to make the app more relevant to Indonesian adolescents.